PRINCIPLES OF DEVELOPING THE SENSE OF SPIRITUAL SOLIDARITY AMONG YOUTH (Modern American Journal of Linguistics, Education, and Pedagogy, 2025)
The article analyzes the main principles of developing a sense of spiritual solidarity among youth, its significance in the process of education and upbringing, and presents effective pedagogical approaches to strengthening it within educational institutions.